Perancangan Prototype Early Warning System pada Kontrol On/Off Belt Conveyor Menggunakan PLC Siemens S7-300 - Taufik; Wahyuni Putri (Jurnal Optimasi Sistem Industri, 2015)
Nowadays, automation system become an important aspect of the manufacturing process because could make integration manufacturing process on it more effective and more efficient. PLC or Programmable Logic Controller is one kind of automation system. Many industries use PLC as automation control device in the manufacturing process to control all kind of process. For example at transportation process of coals in generator industry. Coals could be burned because main elements of coals are carbon, hydrogen, and oxygen. Base on this prototype early warning system design, we get the result if sensor thermocouple detects temperature larger than setpoint temperature (it is 2000C), then PLC will give an order to shut down the output, that is a belt conveyor. The result of this prototype design could use at coals transportation as an early warning system. The design of prototype early warning system could detect and prevent fire because of the consequence of burned coals until spreading of fire could be avoided.